Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura) - Ahyong, Shane T.; Dawson, Elliot W. (Zootaxa, 2006)
The lithodid crab fauna of the Ross Sea, Antarctica, comprises three species in two genera. Two species are new to science: Neolithodes yaldwyni sp. nov. and Paralomis stevensi sp. nov. Neolithodes yaldwyni, previously misidentified from off the Balleny Islands in the Ross Sea as N. brodiei, is morphologically most similar to N. capensis Stebbing, 1905, described from South Africa, differing chiefly in the proportional lengths of the dactyli of the ambulatory legs. Paralomis stevensi is most similar to P. birsteini, differing chiefly by its shorter ambulatory leg dactyli, and in males, the longer ambulatory legs and much larger right cheliped. The third lithodid from the Ross Sea, Paralomis birsteini Macpherson, 1988, is reported from a wide size range of specimens, including an ovigerous female, indicating the presence of a reproductive population in the region. The presence of N. yaldwyni in the Ross Sea is consistent with the hypothesis that lithodids colonized the Southern Ocean via southward movement from low to high latitudes through deepwater. The strong similarity between N. capensis and N. yaldwyni indicates a possible South African–Kerguelen–Antarctica link. The rhizocephalan, Briarosaccus callosus Boschma, 1930, parasitizing P. birsteini, is recorded for the first time from the area.